Karakteristik Fisikokimia dan Antioksidan Minuman Herbal Bunga Telang pada Berbagai Proporsi Daun Rambusa dan Beluntas - Widyawati, Paini Sri; Epriliati, Indah; Purwanto, Agus; Simanjuntak, Melvin Emil (Fakultas Teknologi Pertanian Universitas Jember, 2025)
Pluchea herbal drink has less attractive color and sensory characteristics so that it needs the addition of other herbal ingredients to improve it, especially butterfly pea flowers. Using of butterfly pea flowers at 60% w/w proportion can increase panelist acceptance, but its antioxidant activity is reduced. Therefore, it is necessary to combine pluchea leaves with stinking passion flower leaves to increase its antioxidant activity. The stinking passion flower is a herbal plant that has the potential as an antioxidant because it contains flavonoids, alkaloids, steroids, triterpenoids, saponins, and tannins. The purpose of this study was to determine the physicochemical and antioxidant characteristics of butterfly pea herbal drink in various proportions of stinking passion flower-pluchea leaves. The results showed that increasing the proportion of stinking passion flower leaves did not change the intensity and blue color of the butterfly pea herbal drink, but the turbidity level decreased along with the increase in pH value and the decrease in total acid value. The addition of stinking passion flower leaves up to a proportion of 70% w/w was able to increase the total phenol content (TPC) and antioxidant activity (DPPH free radical scavenging activity and iron ion reducing power/ FRAP), but the total flavonoid content/TFC decreased along with the increase in the proportion of stinking passion flower leaves. The combination of stinking passion flower-pluchea leaves up to a proportion of 70:30 % w/w is the right proportion to increase the total phenol content and antioxidant activity of the butterfly pea flower herbal drink.Keywords: antioxidant, butterfly pea flower, herbal drink, pluchea leaf, stinking passion flower leaf